Pendampingan Penyusunan Laporan Keuangan Berbasis Aplikasi SIAPIK pada UMKM Rumah Makan di Kelurahan Maguwoharjo - Descha Elsa Sunmi; Rochmad Bayu Utomo (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This community service activity was conducted because the quality of bookkeeping and financial reporting in restaurants in Maguwoharjo Village is still relatively low. Profit and loss reports and financial position reports have not been well-designed because many micro, small, and medium enterprises (MSMEs) still record their finances manually. Business owners also cannot differentiate between personal and business finances, which makes it difficult for them to accurately understand their financial situation. The objective of this activity was to help five MSME restaurants (three Padang rice MSMEs, one soto stall, and one lying-down chicken MSME) prepare financial reports using the SIAPIK application. The implementation method included observation, training, mentoring on the use of SIAPIK, and evaluation. The results showed that the use of SIAPIK can improve the regularity of transaction bookkeeping, assist in preparing profit and loss reports and financial position reports, and improve business owners' understanding of their business's financial condition. MSME owners also began to be able to independently record transactions and separate personal and business finances. Thus, digitalization of financial bookkeeping through the SIAPIK application is a solution to help MSME restaurants in Maguwoharjo Village better manage the finances of their businesses.